Effect of the process parameters in the additive manufacturing of in situ Al/AlN samples. (October 2019) - Riquelme, A.; Rodrigo, P.; Escalera-Rodriguez, M.D.; Rams, J.
Highlights: Al and Al/AlN DLD process map have been developed. In situ Al/AlN samples achieved higher mechanical properties than Al samples. Powders form an external porous mold during fabrication that acts as a casting mold. Laser parameters affect on the microstructure and properties of DLD structures. Abstract: Additive manufacturing has revolutionized the manufacturing industry. Researchers have investigated various techniques for increasing the reliability of the metal Additive Manufacturing processes. However, there are few studies about Additive Manufacturing of metal matrix composite components, so, it is necessary increase the research about this topic. In situ Al/AlN composite was synthesized using Direct Laser Deposition equipment in which aluminum powder was deposited through a laser beam using N2 as carrying and reactive gas. This composite powder has been melted and directly deposited layer by layer to form an additive structure. The effect of the laser parameters on the geometry, microstructure and properties of the fabricated structures have been analysed. This allowed the development of a process map for Al and Al/AlN pieces fabricated by Direct Laser Deposition. In situ Al/AlN samples have higher mechanical properties than Al samples.